Sustainable Land Management Practices in Amhara and Oromia Regions - Dira, Samuel Jilo; Girma, Mulye; Matewos, Tafesse; Moreda, Biniyam; Dejene, Melisew; Kassa, Getahun (2023)
Samuel Jilo Dira, Mulye Girma,Tafesse Matewos, Biniyam Moreda, Melisew Dejene, Getahun Kassa REGIONAL WORKSHOP SPIR II Learning Event Co-organized by IFPRI, USAID, CARE, ORDA, and World Vision MAY 16, 2023 - 9:00AM TO MAY 17, 2023 - 5:00PM EAT